Normative and Maladaptive Personality Traits and Self-Reported Executive Functioning. (April 2022) - Roye, Scott; Calamia, Matthew; Castagna, Peter J.; Aita, Stephen L.; Hill, Benjamin D.
Research on self-reported executive functioning (EF) and personality has largely focused on normative personality traits. While previous research has demonstrated that maladaptive personality traits are associated with performance-based EF, the literature examining the relationship between these traits and self-reported EF is limited. The current study examined the relationship between multiple domains of self-reported EF (Barkley Deficits in Executive Functioning Scale) and both normative (The International Personality Item Pool–NEO–120 Item [IPIP-120]) and maladaptive (Personality Inventory for DSM-5 –Short Form [PID-5-SF]) personality traits in an undergraduate student sample ( n = 354). Similar to past research, relationships were largest across EF domains for both measures related to neuroticism (i.e., IPIP-120 neuroticism and PID-5-SF negative affectivity) and conscientiousness (i.e., IPIP-120 conscientiousness and PID-5-SF disinhibition). Normative personality traits generally accounted for greater variance in EF when examined alone and were also generally associated with greater incremental validity when compared with maladaptive personality traits. However, multiple regression analyses indicated that maladaptive personality traits added unique predictive variance above and beyond normative personality traits in their association with multiple domains of EF. These results highlight the utility of assessing both normative and maladaptive personality traits as well as multiple domains of EF to more fully understand the relationship between personality and EF.